Palmar rheumatoid nodulosis associated with local pressure. Issue 8 (August 1992) - Ben-Chetrit, E; Enk, C; Rubinow, A
Abstract : Rheumatoid nodulosis is a term used to describe adult patients with rheumatoid arthritis with little or no clinical joint inflammation who have numerous subcutaneous nodules indistinguishable from those of patients with active rheumatoid arthritis. This paper reports the case of a woman with quiescent rheumatoid arthritis who developed palmar nodulosis three weeks after the strenuous activity of painting her apartment. This case illustrates the direct association between the appearance of nodulosis and physical pressure despite inactive disease.